2019 Marriage Law Triggered “Baby Bust'” An Islamic Legal Perspective On The Decline In Marriage Rates - Yulizain Putra; Elfia; Zulfan (MASADIR: Jurnal Hukum Islam, 2025)
The Marriage Law No. 1 of 2019 in Indonesia has sparked debates on its potential to trigger a "baby bust" phenomenon, characterized by declining marriage rates and fertility. This study examines the Islamic law perspective on how the law's provisions such as raising the minimum marriage age to 19 years contribute to reduced marriages. Employing a qualitative juridical-empirical method, data were gathered through literature review of fiqh texts (mazhab Syafi'i, Hanafi, Maliki, and Hanbali) and empirical analysis of marriage statistics from BPS (2015-2023). Results reveal a 15% drop in marriage rates post-2019, aligned with Islamic principles emphasizing maslahah (public interest) yet conflicting with urfi marriage customs in rural areas. Discussion posits that while the law upholds child protection (hifz al-nasl), it inadvertently discourages early marriages, prompting fatwa adaptations from MUI. Recommendations include harmonizing statutory law with Islamic jurisprudence to mitigate demographic declines.